1998
DOI: 10.1182/blood.v91.7.2264.2264_2264_2271
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 and JAK1 Constitutively Associate With an Interleukin-5 (IL-5) Receptor α and βc Subunit, Respectively, and Are Activated Upon IL-5 Stimulation

Abstract: The human interleukin-5 receptor (hIL-5R) consists of a unique α subunit (hIL-5Rα) and a common β subunit (βc) that activate two Janus kinases (JAK1 and JAK2) and a signal transducer and activator of transcription (STAT5). The precise stoichiometry of the hIL-5R subunits and the role of JAK kinases used in IL-5 signaling were investigated. We analyzed the interaction between hIL-5Rα and βc by immunoprecipitation using anti–hIL-5Rα and anti-βc monoclonal antibodies. The binding of JAK1 and JAK2 to each hIL-5R s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…4B, bottom panel, and Fig. 5A, third panel from top) [35,36]. Last, the data demonstrate that the molecular signals, which initiate ␤c ubiquitination and proteasome degradation, are early events mediated by JAK kinases and not downstream events mediated by the MAPK, PI-3K, and the p38 MAPK signaling pathways.…”
Section: Role Of Lyn Kinase In ␤C Ubiquitination and Proteasome Degramentioning
confidence: 74%
“…4B, bottom panel, and Fig. 5A, third panel from top) [35,36]. Last, the data demonstrate that the molecular signals, which initiate ␤c ubiquitination and proteasome degradation, are early events mediated by JAK kinases and not downstream events mediated by the MAPK, PI-3K, and the p38 MAPK signaling pathways.…”
Section: Role Of Lyn Kinase In ␤C Ubiquitination and Proteasome Degramentioning
confidence: 74%
“…Several distinct signaling cascades are involved in cell proliferation and maturation in the IL-5 receptor-signaling pathway. IL-5 activates a number of kinases, including Bruton-type tyrosine kinase (Btk), Janus kinase (Jak2), Lyn and Raf-1, as well as the phosphatase SHP2 [24][25][26][27][28]. Among these, Btk and Jak2 are essential for proliferation of B-lineage cell lines [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…30 Detailed studies of the truncated cytoplasmic domain of human IL-5Ra revealed that the cytoplasmic stretch at position 346±387, containing the ppvp motif, is necessary for JAK2 binding. 26 Moreover, our deletion analysis revealed that six amino acid residues in the carboxyl-terminal (DC3) region of IL-5Ra appear to be dispensable for IL-5-induced cell proliferation. 29 Thus far, functional analyses of the IL-5Ra have been carried out using in vitro proliferation assays with cultured cell lines altered by conventional gene transfection experiments.…”
Section: Introductionmentioning
confidence: 89%